Automated two-way coupling of CFD fire simulations to thermomechanical FE analyses at the overall structural level. (March 2018) - Feenstra, J.A.; Hofmeyer, H.; Van Herpen, R.A.P.; Mahendran, M.
Abstract: Coupled CFD fire simulations and thermomechanical FE analyses typically consist of fire simulations, heat transfer analyses and structural response analyses, mutually coupled by three coupling steps. There are two coupling approaches, one-way and two-way coupling, where two-way coupling includes the effects of the structural response on fire propagation. In the first part of this paper, one- and two-way coupling approaches including the coupling steps are proposed to include coupling at the structural level. Then a case study comprising an office space with a 12-plate thin-walled steel façade under fire conditions is introduced, as well as the related CFD and FE models. A newly developed automated coupling interface and subprograms are used to perform several one-way and two-way coupled analyses using a coarse and fine CFD mesh for the case study. Slight differences are found in the results of identical simulations due to random effects in the fire simulations. Nevertheless, it can be concluded that two-way coupling is feasible, and that significant differences in the façade failure progression illustrate its effectiveness. Future research includes additional developments of both the fire and structural models, as well as verification and parametric studies to further confirm the findings. Highlights: One- and two-way coupling approaches including their coupling steps are proposed to include coupling at the structural level. A case study is carried out that comprises an office space with a 12-plate thin-walled steel façade under fire conditions. Two-way coupling is feasible, and significant differences in the façade failure progression illustrate its effectiveness. Verification is needed by tests for the mutual influence of fire and structural behaviour at the overall structural level.